The moderating role of trust and commitment between consumer purchase intention and online shopping behavior in the context of Pakistan - Shafique Ur Rehman; Anam Bhatti; Rapiah Mohamed; Hazeline Ayoup (Journal of Global Entrepreneurship Research, 2019)
The purpose of this research is to determine the relationship between theory of planned behavior (TPB) and technology acceptance model (TAB) elements and consumer purchase intention. Consumer purchase intention mediates the relationship between TPB and TAM elements and online shopping behavior. Moderating role of trust and commitment determined between consumer purchase intention and online shopping behavior. PLS-SEM technique used in analyzing data that collected from students and lecturer of the higher education commission (HEC) recognized universities in Punjab, Pakistan. The current research attempts to examine the role of perceived usefulness, perceived ease of use, attitude, subjective norms, perceived behavioral control, trust, commitment, and consumer purchase intention in predicting actual behavior of consumers by integrating three pre-established frameworks of TAM and TPB theory. Findings reveal that perceived usefulness, perceived ease of use, attitude, subjective norms, and perceived behavioral control have a positive and significant influence on consumer purchase intention. Consumer purchase intention (CPI) mediates between all five independent constructs and online shopping behavior (OSB). Commitment and trust significantly moderate the relationship between consumer purchase intention and internet shopping behavior also has a direct influence on online shopping behavior.
Keywords: 650; TPB; TAM; Trust; Commitment; Consumer purchase intention; Online shopping behavior